The Impact of Operating Room Distractions on Stress, Workload, and Teamwork. Issue 6 (June 2015) - Wheelock, Ana; Suliman, Amna; Wharton, Rupert; Babu, E. D.; Hull, Louise; Vincent, Charles; Sevdalis, Nick; Arora, Sonal
<x xml:space="preserve">Abstract</x> Objective: To investigate whether distractions in the operating room (OR) are associated with higher mental workload and stress, and poorer teamwork among OR personnel. Background: Engaging in multiple tasks can affect performance. There is little research on the effect of distractions on surgical team members' behavior and cognitive processes. Methods: Ninety general surgery cases were observed in real time. Cases were assessed by a surgeon and a behavioral scientist using 4 validated tools: OR Distractions Assessment Form, the Observational Teamwork Assessment for Surgery tool, NASA-Task Load Index, and short form of the State Trait Anxiety Inventory. Analysis of variance was performed to evaluate significant differences between teamwork, workload, and stress level among team members. Correlations (Pearson r) were computed to evaluate associations between variables. Results: The most prevalent distractions were those initiated by external staff, followed by case-irrelevant conversations. Case-irrelevant conversations were associated with poorer team performance. Irrelevant conversations initiated by surgeons were associated with lower teamwork in surgeons (across team skills: r = −0.44 to −0.58, P < 0.05 to 0.01) and anesthesiologists (r = −0.38 and r = −0.40, for coordination and leadership; P < 0.05). Equipment-related distractions correlated with higher stress (r = 0.48, P < 0.05) and lower teamwork (across team skills: r = −0.42 to −0.50, P < 0.05) in nurses. Acoustic distractions correlated with higher stress in surgeons (r = 0.32, P < 0.05) and higher workload in anesthesiologists (r = 0.30, P < 0.05). Conclusions: Although some distractions may be inevitable in the OR, they can also be detrimental to the team. A deeper understanding of the effect of distractions on teams and their outcomes can lead to targeted quality improvement.